Análisis jurídico y doctrinario de los procedimientos para las medidas de seguridad impuestas a las personas inimputables por trastornos mentales - Riofrio Mantilla, Jairo Lenin (2024)
The present thesis, entitled "Legal and Doctrinal Analysis of Procedures for Security Measures Imposed on Mentally Impaired Individuals," is based on a study of the application of security measures stipulated in the Comprehensive Organic Penal Code and their effectiveness. It is evident that individuals with mental disorders who are undergoing legal proceedings are sentenced to punishment without receiving comprehensive psychiatric treatment, thus violating their rights, particularly the right to health. In Ecuador, there is a constitutional norm guaranteeing the right to health as a fundamental duty, as well as criminal laws that establish security measures for mentally impaired individuals undergoing legal proceedings. However, it is considered that this legal framework is not sufficient to effectively implement the Comprehensive Organic Penal Code. Among the findings identified in the study, it is observed that there is legislation involving the treatment of mentally impaired individuals in specialized care centers. However, in reality, there is a lack of specialized psychiatric hospitals that work comprehensively, ensuring rehabilitation for the mentally ill. It is recommended that Article 76 of the Comprehensive Organic Penal Code be reinforced, prioritizing comprehensive treatment for the mentally ill and ensuring the effectiveness of the law.